2019
DOI: 10.2169/internalmedicine.0317-17
|View full text |Cite
|
Sign up to set email alerts
|

Successful Cord Blood Transplantation in a Werner Syndrome Patient with High-risk Myelodysplastic Syndrome

Abstract: Werner syndrome (WS) confers a high risk of the development of neoplasias, including hematological malignancies, and curative treatment for these malignancies is difficult to achieve. A 44-year-old man with myelodysplastic syndrome was admitted to our hospital. He was diagnosed with mutation-proven WS. He underwent cord blood transplantation (CBT) following fludarabine, busulfan, and melphalan administration. A chimerism analysis of his marrow blood on day 62 showed a donor pattern >95%, which confirmed engraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Cord blood transplantation (CBT) has some effects on the MDS of Werner syndrome. A 44year-old male patient with MDS underwent CBT and obtained a 15-month survival period, during which time he had MDS remission and no treatment-related toxicity (15). Allogeneic hematopoietic cell transplantation (HCT) may be feasible for Werner syndrome-related AML, and an 18-year-old female patient with AML obtained a 5-year survival after HCT without severe chemotherapy or transplant-induced toxicities (16).…”
Section: Discussionmentioning
confidence: 99%
“…Cord blood transplantation (CBT) has some effects on the MDS of Werner syndrome. A 44year-old male patient with MDS underwent CBT and obtained a 15-month survival period, during which time he had MDS remission and no treatment-related toxicity (15). Allogeneic hematopoietic cell transplantation (HCT) may be feasible for Werner syndrome-related AML, and an 18-year-old female patient with AML obtained a 5-year survival after HCT without severe chemotherapy or transplant-induced toxicities (16).…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, three To the best of our knowledge, this is the first description of successful alloHCT in a young adult patient with WS-related AML, who is alive and in remission several years after transplantation. Hayashi et al previously reported a patient with WS and high-risk MDS undergoing alloHCT [9]. The conditioning regimen consisted of fludarabine, busulfan and melphalan followed by cord blood transplantation.…”
mentioning
confidence: 99%